The impact of human resource factors on lightning safety performance - Hajikhani M.; Izadi M.; Kadir M.Z.A.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Personnel; Safety engineering; Incentive and rewards; Iranian companies; Manufacturing companies; Organizational factors; Organizational levels; Safety guidelines; Safety performance; Lightning